Regenerating Muslim inventors – the present future - Nordin, Anis Nurashikin; Ramli, Nabilah (Universiti Sains Islam Malaysia, 2020)
Much discussion has been done about the golden era of Muslim civilization and its decline over the past centuries. Recent downturn of events in the Middle East has given birth to the Muslim refugee crisis, coupled with terrorist attacks have fueled the growth. Now more than ever, Muslim need inspirational role models, to survive this crisis and backlash. This paper intends to highlight the achievements of Muslim scientists, engineers and innovators, dating from the early 9th century to the more recent 21st century. Some of the works discussed in this paper are not so commonly discussed, such as the work of Banu Musa on control theory and mechanical pumps by Al-Jazari. Next special highlight is done on the works of Muslim Nobel Prize winners as well as their attempts to encourage other Muslims to be involved in science and technology. Finally, we discuss the successful Muslim inventors of the 21st century, both who created modern devices for communications and lasers. The paper concludes with a critical discussion on what are the qualities that these Muslim technologists had to succeed and how the modern generation can emulate them.